The Corralation between Knowledge and Satisfaction Level with the High Referral of Patients Participating in the National Health Insurance (NHI) at First Level Health Facilities (FLHF) - Werdana, Andi; Rendita Dwibarto; Siswanto (Institut Citra Internasional, 2024)
A health service that regulates the delegation of duties and responsibilities for health services that cannot be implemented at the basic (primary) service level due to limited infrastructure, medical personnel and the presence of anamnesis that requires patients to receive further health services such as specialist services. The still high number of patient referrals shows that community health centers are not yet able to provide optimal health services as gatekeepers of health services in the community. The aim of the research is to analyze factors related to patient referrals for National Health Insurance (JKN) participants at First Level Health Facilities (FKTP). The research design used was analytical survey research with a cross sectional approach. The sample was 109 patients participating in National Health Insurance (JKN) who received services at the Gerunggang Community Health Center, Pangkalpinang City. The research results show a relationship between Knowledge and Referrals from JKN Participant Patients, namely p value = 0.000 < ? = 0.05 and there is a relationship between Satisfaction Level and Referrals from JKN Participant Patients, namely p value = 0.018 < ? = 0.05. The research conclusion is that there is a relationship between knowledge and the level of patient satisfaction with patient referrals for JKN participants at the Gerunggang Community Health Center. It is hoped that health workers at Community Health Centers, both medical and non-medical personnel, will always improve services and prioritize patient needs, especially in providing referral information to patients.